UV Spectrophotometric Determination of Aripiprazole in Bulk and Pharmaceutical Formulation - R. Kalaichelvi; B. Thangabalan; D. Srinivasa Rao; E. Jayachandran (E-Journal of Chemistry)
A simple, sensitive and reproducible spectrophotometric method was developed for the determination of aripiprazole in pure form and in pharmaceutical formulation. It has an absorption maximum at 219 nm and obeys beer's law in the concentration range 2- 10 µg mL-1. Results of analysis were validated statistically and by recovery studies. The apparent molar absorptivity and sandell's sensitivity were 5.2 x 105 L mol-1 cm-1 and 8.4 x 10-3 µg cm-2, respectively. The slope and intercept of the equation of the regression line are 0.0035 and 0.1155 respectively. Correlation coefficient was found to be 0.9998. This method is successfully employed for the determination of aripiprazole in pharmaceutical preparation.